Global burden and trends of major mental disorders in individuals under 24 years of age from 1990 to 2021, with projections to 2050: insights from the Global Burden of Disease Study 2021 - Liu, Wei; Zhang, Yu; Chen, Jie; Li, Xiayang; Huang, Yishuai; Zhao, Fuyang; Chen, Fangyao; Qu, Pengfei; Li, Yajun (Frontiers in Public Health, 2025)
BackgroundMental disorders are the leading cause of global non-fatal disease burden, with rising prevalence among children, adolescents, and youth. This study analyzed location-, age-, and sex-specific estimates for nine mental disorders from 1990 to 2021 using GBD 2021 data, projecting burden to 2050.MethodsMethods included calculating average annual percentage change (AAPC) and annual percentage change (APC) for age-standardized prevalence rate (ASPR) and disability-adjusted life years rate (ASDR), alongside decomposition, inequality, frontier, comparative risk, and Bayesian age-period-cohort analyses.ResultsCompared to 1990, the 2021 global burden significantly increased among youth [the AAPC of ASPR = 0.15, 95% confidence interval (CI): 0.14 to 0.16; the AAPC of ASDR = 0.40, 95% CI: 0.29 to 0.51], accelerating sharply after 2019 (the APC of ASPR = 4.74, 95% CI 4.55 to 4.93; the APC of ASDR = 6.64, 95% CI 4.88 to 8.42). Males experienced a higher burden than females, with variations in sex-specific patterns across age groups. Burden varied substantially by socio-demographic index (SDI), being highest in high-SDI regions [ASPR = 12913.13, 95% uncertainty interval (UI): 11135.82 to 14874.98; ASDR = 1750.41, 95% UI: 1253.46 to 2328.87]. We found that the burden changes of nine mental disorders vary at the global, regional, and national levels. Decomposition analysis highlighted that the changes in prevalence and the disability-adjusted life years (DALYs) were predominantly driven by population growth (84.86% and 57.92%), with the most significant improvements observed in higher SDI regions. Frontier analysis revealed the potential for burden reduction in higher income countries and territories. Globally, key risk factors included childhood sexual abuse, bullying, intimate partner violence, and lead exposure were identified for anxiety disorders, depressive disorders, and idiopathic developmental intellectual disability, respectively. Projections indicated that the burden of mental disorders is likely to continue its decline in 2050 (ASPR = 6120.71 per 100,000, 95% CI: 3973.57 to 8267.85; ASDR = 844.71 per 100,000, 95% CI: 529.48 to 1159.94).ConclusionDespite projected rate declines by 2050, the global burden of mental disorders is increasing, with significant disparities across populations and a recent surge demanding intensified prevention and equitable healthcare expansion worldwide.